Evaluation of rat tissue response to Guedes-Pinto and calcium hydroxide pastes by morphological analysis of repair in rat's tooth socket - Takahashi, Karine; Maltempi Filho, Paulo; Cunha, Robson Frederico [UNESP]; Dezan Junior, Eloi [UNESP] (Dental Press International, 2015)
In order to evaluate late biological response of two types of filling material of deciduous teeth, calcium hydroxide and Guedes-Pinto pastes, the implantation technique in rat sockets was employed. For morphological analysis, carried out after 7 and 28 days, 48 rats had their maxillary right central incisor removed, and a polyethylene tube implant containing one of the pastes was placed into the socket. On the 7th day, calcium hydroxide paste caused greater edema than Guedes-Pinto paste, and both types of material showed connective tissue with fibroblasts and blood vessels, with macrophages and lymphocytes. On the 28th day, calcium hydroxide paste had connective tissue with a large amount of macrophages and lymphocytes near the material, whereas in further areas, it had neofomed trabeculae. For the Guedes-Pinto paste, there were neoformed bone trabeculae nearby. The latter were found in larger amounts in areas further from the material surface. Guedes-Pinto paste caused less edema and provided less interference in the repair process.
Keywords: Calcium hydroxide; Deciduous tooth; Root canal filling material; Root canal therapy